Environmental Degradation in Nigeria: A Christian Ethical Approach - Atoi, Ewere Nelson; Olowoyeye, Emmanuel Olurokan; Jacob, Lembi Jamima (NIU Journal of Humanities, 2023)
Environmental degradation is a serious issue confronting different societies the world over in contemporary times. It has continued to impact negatively on the quality of life in many parts of Nigeria. Previous studies on environmental degradation in Nigeria have laid more emphasis on the scientific and technological perspectives with little attention given to the Christian ethical dimension. Religion can play a vital role in influencing attitudes, behavior, perceptions, modes of coping and actions in response to environmental problems, but it has been largely ignored in Nigerian ecological discourses. This essay therefore, examines environmental degradation in Nigeria from Christian ethical perspective with a view to address environmentally harmful human actions in the Nigerian ecological space through the lens of Christian ethical norms. Data was obtained from existing scholarly literature, media reports, and careful observations of the contemporary environmental crisis in Nigeria. Content, critical, and constructive methods of analysis were utilized for data interpretation. This paper avows that there are both natural and human causes of environmental degradation. Howbeit, human causes are more than the natural. It was uncovered that humans have continued to exploit nature through the irresponsible use of natural resources. This essay submits that environmental degradation problems in Nigeria can be effectively address through Christian stewardship, eco-justice and creation spirituality, which are the emerging environmental ethical ideologies in contemporary Christianity and other Christian ecological values inherent in the bible. Nigerian Christians must become ambassadors of these environmental ethical principles for effective ecological healing in the country. Keywords: Environmental Degradation, Christian Ethical Perspective, Humans, Natural Resources, Ecological Healing.